Rethinking Economic Discrimination - S, Jomo K (American Economic Review, 2003)
Forms of Intolerance held in early September 2001 was unfortunately obscured by the tragic events of September 11. Nonetheless, the event reflects global recognition of problems of racial, ethnic and cultural discrimination, oppression and exploitation. The following analysis, inspired by participation in collaborative international research presented to the Conference, suggests that economic discrimination may be usefully seen in terms of rents and rent-seeking. By successfully discriminating against a particular group, employers or consumers succeed in extracting rents from the group discriminate against. However, such rents are different in nature. Discriminated employees (e.g. Blacks) receive lower remuneration or inferior terms of employment. Successful discrimination allows employers to use their availability to extract additional ‘producer surplus ’ by conceding lower (‘intermediate’-level) wages or employment conditions to ostensibly privileged employees (e.g. Whites), than might be the case in the absence of discrimination. Even if there is an eventual equalization of wage rates or employment conditions between the group discriminated against and the privileged group, a ‘producer surplus ’ from the poorer wages or employment conditions may well persist